2021
DOI: 10.1186/s13567-021-01019-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new amino acid mutation in the HN protein of NDV involved in pathogenicity

Abstract: The fusion (F) and haemagglutinin-neuraminidase (HN) proteins of Newcastle disease virus (NDV) are viral entry proteins and are recognized as the major virulence determinants. Previously, a lentogenic NDV virus (CE16) was derived from a mesogenic strain (CI10) through sequential passages in chick embryos. Whole-genome sequence analysis revealed that the two homologous strains shared the same F protein but differed in HN with two amino acid (aa) substitutions (A215G and T430A). To elucidate the molecular reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Studies on other paramyxoviruses have proved that single aa mutations on HN, P, and L proteins have important biological significance. For instance: Studies on the Newcastle disease virus in the family Paramyxoviridae have shown that a single aa mutation in HN significantly altered the viral pathogenicity [35]; studies on the human parainfluenza virus type 3 have shown that a single aa mutation in L can regulate the levels of virus gene expression [36]. Therefore, the specific effects of the aa mutations in HN, P, and L proteins on the biological characteristics of the yak BPIV3 need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other paramyxoviruses have proved that single aa mutations on HN, P, and L proteins have important biological significance. For instance: Studies on the Newcastle disease virus in the family Paramyxoviridae have shown that a single aa mutation in HN significantly altered the viral pathogenicity [35]; studies on the human parainfluenza virus type 3 have shown that a single aa mutation in L can regulate the levels of virus gene expression [36]. Therefore, the specific effects of the aa mutations in HN, P, and L proteins on the biological characteristics of the yak BPIV3 need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that mutations in the HN protein are considered as determinants of in vivo biological activities, such as virulence and pathogenicity [43,44]. We have previously demonstrated that the aa mutations in the HN protein were required for the virulence and pathogenicity of genotype III NDV, but the research content needs to be further enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Молекулярная основа сайта расщепления белка F (FCS) определяет патогенность штаммов NDV: лентогенный вирус в сайте CS содержит меньше основных аминокис-МЕЖДУНАРОДНЫЙ ЖУРНАЛ ПРИКЛАДНЫХ И ФУНДАМЕНТАЛЬНЫХ ИССЛЕДОВАНИЙ № 10, 2023 13  БИОЛОГИЧЕСКИЕ НАУКИ  лот и лейцин в положении 117 [40], мезогенный и велогенный штаммы имеют многоосновную аминокислоту CS с фенилаланином в положении 117 [41]. Специфическая аминокислотная последовательность белка F тесно связана с тропизмом по отношению к тканям мозга, легких и селезенки [42]. Таким образом, аминокислота в месте расщепления белка F является основным фактором, определяющим вирулентность [43].…”
Section: результаты исследования и их обсуждениеunclassified